Modeling of structural and thermodynamics properties of sigma-phase for the Fe-Cr system - Udovskya A.; Kupavtseva M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The three- sub-lattice model (3SLM) for description of atom’s distribution of two components with different coordination numbers (12, 14 and 15), into s-phase structure depended on composition and temperature is depictured in this paper. Energetic parameters of 3SLM were calculated by fitting procedure fixed to results obtained by ab-initio calculations conducted for paramagnetic states of differently ordered complexes stayed at the sigma-phase’s crystal structure for Fe-Cr system at 0 K. Respective algorithm and computer program have allowed to calculate an atom distribution of components upon the sub-lattices of s-phase at 300 - 1100 K. There is satisfactory agreement between calculated results and the experimental data obtained by neutron and structural research methods. Obtained results demonstrate satisfactory agreement between calculated and experimental data of BCC solutions and sigma - phase of the Fe-Cr system stayed at an equilibrium state.